Response of exotic sorghum (Sorghum bicolor [L.] Moench) cultivars to planting date under natural infestation of Striga hermonthica (Del) Benth. in the Sudan savanna zone of northeast Nigeria - Kamara, A.Y.; Ekeleme, F.; Omoigui, L.O.; Menkir, A.; Chikoye, David; Dugje, I.Y. (Informa UK Limited, 2011)
Sorghum (Sorghum bicolor [L.] Moench) is one of the most important cereal crops grown in the dry savannas and semi-arid regions of West Africa under rain-fed conditions. Although total sorghum production in Nigeria has increased over the years, the average grain yield on farmers' fields has remained low. A two-year trial was conducted to evaluate the effect of planting dates on three exotic sorghum cultivars (P9402, P9405, and PSL985061) and an improved local cultivar (KSV 8) under natural infestation with Striga hermonthica in northeast Nigeria. At Nzuda, the highest yield was obtained when planting was carried out on 19 July 2006 and on 5 July 2007. The decline in yield in 2007 as planting dates increased was largely due to early cessation of rain, which affected grain yield. At Sabon-Gari, KSV 8 and P9402 produced comparable grain yields that were higher than the yields of other cultivars at all planting dates. Grain yields of KSV 8 and P9402 were greater for 5 July than for the other planting dates and decreased significantly as the planting date was delayed, probably due to long maturity period. The highest grain yields were obtained from P9405 and PSL985061 when planted on 12 July and 19 July, respectively. KSV 8 had the highest number of emerged Striga plants at both locations. The number of emerged Striga plants under KSV 8 was 4.0–5.1 times higher at Nzuda and 2.4–2.6 times higher at Sabon-Gari than the number on the exotic cultivars at those locations. Among the exotic cultivars, differences in the number of emerged Striga plants were not significant. Farmers in the zone would maximize sorghum yield if improved cultivars are planted at the appropriate dates in Striga infested fields.